Analisis Konektivitas Udara Dan Pengembangan Rute Penerbangan di Bandar Udara Internasional Singkawang - Aditya, Ilham; Anisa, Khairun; Al Ashari, Khoiri Akbar; Yardan Pandya, Luthfi; Sandy Dwi, Marselinus; Azhar Rifandy, Mokhamad (aspal, 2025)
Air transportation has an important role in supporting regional economic growth, especially for areas with tourism and trade potential such as Singkawang City. This study analyzes the contribution of improving connectivity and developing flight routes at Singkawang International Airport to local economic growth. Using qualitative descriptive research methods, data is collected through literature studies, documentation, and secondary data from official sources. The results of the study show that this airport has the potential to serve domestic and international routes, and is an important factor in strengthening the trade and tourism sector. However, challenges such as low flight frequencies, lack of airline incentives, and lack of intermodal integration remain major obstacles. Recommended strategies include on-demand route development, integration with local leading sectors, partnerships between stakeholders, and the use of spatial data for route planning. This study confirms that planned and adaptive air connectivity can be a significant driver in realizing regional economic development in an inclusive and sustainable manner.